Heterogeneously catalyzed strategies for the deconstruction of high density polyethylene: plastic waste valorisation to fuels - Burange, Anand S.; Gawande, Manoj B.; Lam, Frank L. Y.; Jayaram, Radha V.; Luque, Rafael (Green Chemistry, 2015)
The plastic industry generates enormous quantities of plastics at projected rates (both production and consumption) which can significantly threaten our environment in terms of plastic waste generation. High density polyethylene (HDPE) is one of the main fractions of municipal solid waste which has a remarkable potential to be valorised into fuels (e.g. bio-oils). Catalytic degradation is an innovative alternative process to transform plastic waste into such value added products. This mini review was aimed to discuss the most relevant and recent catalysts developed for the catalytic degradation of HDPE including metal oxides, sulphated metal oxides, zeolites, nanostructured zeolites, molecular sieves, fluid catalytic cracking (FCC) catalysts, metal carbonates and mesoporous materials for the production of chemicals and fuels (e.g. diesel and gasolines). Activities and selectivities as well as important effects of additives, particle size, catalyst to polymer ratios and also recent approaches for waste management will be discussed.